Cardiac safety of tiotropium in patients with COPD: a combined analysis of Holter‐ECG data from four randomised clinical trials. Issue 1 (11th December 2014) - Hohlfeld, J. M.; Furtwaengler, A.; Könen‐Bergmann, M.; Wallenstein, G.; Walter, B.; Bateman, E. D.
Summary Background Tiotropium is generally well tolerated; however, there has been debate whether antimuscarinics, particularly tiotropium administered via Respimat® Soft Mist™ Inhaler, may induce cardiac arrhythmias in a vulnerable subpopulation with cardiovascular comorbidity. The aim of this study was to provide evidence of the cardiac safety of tiotropium maintenance therapy. Methods Combined analysis of Holter electrocardiogram (ECG) data from clinical trials of tiotropium in chronic obstructive pulmonary disease (COPD). Trials in the Boehringer Ingelheim clinical trials database conducted between 2003 and 2012, involving tiotropium HandiHaler® 18 μg and/or tiotropium Respimat® (1.25‐, 2.5‐, 5.0‐ and 10‐μg doses) were reviewed. All trials involving Holter‐ECG monitoring during this period were included in the analysis. Men and women aged ≥ 40 years with a smoking history of ≥ 10 pack‐years, and a clinical diagnosis of COPD were included. Holter ECGs were evaluated for heart rate (HR), supraventricular premature beats (SVPBs), ventricular premature beats (VPBs) and pauses. Quantitative and categorical end‐points were derived for each of the Holter monitoring days. Results Four trials (n = 727) were included in the analysis. Respimat® (1.25–10 μg) or HandiHaler® (18 μg) was not associated with changes in HR, SVPBs, VPBs and pauses compared with placebo or the pretreatment baseline period. In terms of cardiac arrhythmia end‐points, there was no evidence for an exposure–effect relationship. Conclusions In this analysis, tiotropium maintenance therapy administered using Respimat® (1.25–10 μg) or HandiHaler® (18 μg) once daily for periods of up to 48 weeks was well tolerated with no increased risk of cardiac arrhythmia in patients with COPD.